Gratitude, Self-Esteem and Optimism in People with Physical Disabilities - Rini LESTARI; Maharani FAJAR (Prizren Social Science Journal)
The psychological problems experienced by people with physical disabilities are feeling hopeless and uncertain of their future. They feel the future will be dismal. They also feel afraid of not having proper education, jobs, and place in society, not be able to work normally, fail in lives, rejected, and not be able to give the best to their loved ones. This condition indicates non-optimistic. Optimism is an essential psychosocial resource for protecting the health and influencing human functioning. The purpose of this study is to examine the relationship between gratitude and self-esteem with optimism in people with physical disabilities. The samples of this study were people with physical disabilities, aged 18 - 35 years old, attended social rehabilitation and totaled 106 people. Data collection methods were gratitude scale, self-esteem scale, and LOT-R. Analysis of the data used multiple regression analysis. The analysis indicates that there is  a  significant relationship between gratitude and self-esteem with optimism in people with physical disabilities. The contribution of gratitude and self-esteem variables to optimism is 48.1%. People with physical disabilities have optimism and gratitude in the high category, while self-esteem in the medium category.